Materialising New Forms of Journalism: A Process Model. Issue 3 (16th March 2023) - Doherty, Skye; Johnston, Jane; Matthews, Ben
Abstract: Design is a discipline that gives form to alternative futures. Through a process of material exploration, it explores novel configurations of technology, people and values, and in doing so, seeks to understand the implications of new designs. It is this practice of making and creating that is valuable to journalism as it grapples with how to respond to communication technologies that are increasingly subtle, physical and sensuous. In this article we examine the theory of materiality as it has been discussed in communication and design literature, proposing a conceptual approach for a design-led view of materiality in journalism studies. This view sees materiality from a form-giving perspective in which technologies and journalistic principles are materials to shape in order to explore potentials and possibilities. This article extends the concept of journalism design by examining how journalistic values can be incorporated into the design of public interest technologies. In doing so, it frames journalism as a process of designing things that respond to public concerns. The article also contributes to scholarship that sees tinkering, iteration and participation as a way to understand how news could be structurally different.